Predictors of Bilateral SLN Radiocolloid Detection in Endometrial Carcinoma - Jankulovska, Anamarija; Stojchevski, Sasho; Aluloski, Igor; Tanturovski, Mile; Manevska, Nevena; Daneva Markova, Ana; Stojanoski, Sinisha (Georg Thieme Verlag KG, 2023)
Introduction  Sentinel lymph node (SLN) mapping is an alternative method to conventional lymphadenectomy for nodal status assessment in patients with stage I/II endometrial carcinoma (EC). This study aimed to analyze the potential predictors of unsuccessful bilateral detection of SLN after the application of radiocolloid in EC. Materials and Methods  A prospective, observational, cross-sectional study was performed on 41 patients with EC in preoperative stage I, who underwent SLN mapping after cervical application of 4mCi 99m Tc-SENTI-SCINT. The demographic, clinical, and tumor-related data were obtained from the patient's medical records. Univariate analysis was used to analyze the potential factors associated with an unsuccessful bilateral SLN biopsy. Results  The bilateral SLN detection rate of planar lymphoscintigraphy, single photon emission computed tomography/computed tomography, and gamma probe was 29.26, 41.46, and 26.82%, correspondingly. None of the 16 analyzed risk factors showed statistical significance for nonconclusive bilateral SLN biopsy. Conclusion  Larger scale studies are needed to determine the exact risk factors for unsuccessful bilateral mapping of the lymphatic drainage after cervical application of the radiotracers. This will eventually lead to improvement in bilateral SLN detection in EC patients, so unilateral lymphadenectomy could be avoided.